2011
DOI: 10.1016/j.jnucmat.2010.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of E×B driven transport on the deposition of carbon in the outer divertor of ASDEX Upgrade

Abstract: Reversal of the toroidal magnetic field and plasma current is observed to considerably change the re-deposition of 13 C injected into the outer divertor scrape-off layer of ASDEX Upgrade. In forward field low-density L-mode plasmas, 24-32% of injected carbon is found locally re-deposited. The deposition tails are aligned toroidally both upstream and downstream of the exit holes and indicate transport towards the strike point. In reversed field with similar main plasma parameters, the re-deposition efficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The deposition efficiencies reported earlier for Ex fwd [4] and Ex rev [5] are recalculated Figure 2. Calculated injection rates from pressure measurements with the baratron installed in the methane reservoir (top) [4].…”
Section: Experimental Results From Local 13 C Injection Experiments Imentioning
confidence: 99%
See 1 more Smart Citation
“…The deposition efficiencies reported earlier for Ex fwd [4] and Ex rev [5] are recalculated Figure 2. Calculated injection rates from pressure measurements with the baratron installed in the methane reservoir (top) [4].…”
Section: Experimental Results From Local 13 C Injection Experiments Imentioning
confidence: 99%
“…Recently, large discrepancies were found when comparing these rates with the in-vessel pressure measurements in AUG [5]. More dedicated recalibration efforts, by means of a two chamber experiment, have shown that the measurements inside the gas chamber underestimate the actual injection rate by a factor of ∼3, see figure 2.…”
Section: Experimental Results From Local 13 C Injection Experiments Imentioning
confidence: 99%
“…Particularly at the locations of 13 CH 4 injection, both the absolute value and the gradients along the target are reproduced in the simulations for all three measured quantities. T pk e,ot is reduced compared to previous modelling efforts in [13,14], which is largely a result of changes in assumptions for P in , n sep , and cross-field transport, with minor contribution from code development. The LP data do not cover the whole strike point and, thus, cannot be used to verify the modelled density peak at that location.…”
Section: Divertor Conditions In Forward Fieldmentioning
confidence: 92%
“…For local impurity modelling the leading European code is ERO [8,9] -a 3D Monte Carlo impurity transport code that has been applied to several limiter and divertor tokamaks as well as linear plasma experiments, see, e.g., [10][11][12][13][14][15] . ERO depends crucially on high-quality data for PWI as well as for dissociation, ionization and emission data for impurities in the plasma.…”
Section: Introductionmentioning
confidence: 99%